Comparison of 1α-25-dihydroxyvitamin D3 and IgE Levels between Allergic Rhinitis Patients and Healthy People - Demir, Mehmet Gokhan (International Archives of Otorhinolaryngology, 2018)
Introduction Allergic rhinitis is one of the most common allergic diseases that cause a decrease in quality of life. Over the last decades, the increase in the number of cases is supposed to be a result of industrialization and lifestyle changes. Vitamin D, which is a steroid hormone, has a significant immunomodulatory and antioxidant role in the human body.Objective The objective of the present study is to investigate the role of 1α-25-dihydroxyvitamin D3 levels in allergic rhinitis patients and to compare them to the levels found in the healthy population.Methods A total of 256 participants were included in the present study. Allergic rhinitis is diagnosed with the help of the Allergic Rhinitis and Its Impact on Asthma (ARIA) guidelines confirmed through skin prick tests. Control subjects were selected among people without allergy history, which was also confirmed through skin prick tests. The levels of 1α-25-dihydroxyvitamin D3, immunoglobulin E (IgE), and eosinophil counts were measured in blood samples from both groups.Results The mean value of serum levels of 1α-25-hydroxyvitamin D3 was 25.5 ± 3.74 in the allergic rhinitis group, and 31.58 ± 3.85 in the control subjects. This difference reveals statistically-decreased levels in the allergic rhinitis group (p < 0.05). The total IgE levels are increased in the allergic rhinitis group (p < 0.05) and negatively correlated with the serum levels of 1α-25-hydroxyvitamin D3 (r = - 0.259, p < 0.05).Conclusion Lower serum levels of 1α-25-hydroxyvitamin D3 were detected in the allergic rhinitis population. This data is also correlated to the IgE response in the study group. A supplement of 1α-25-hydroxyvitamin D3 in deficient patients might be helpful to relieve symptoms and signs of allergic rhinitis, but further studies are needed.
Keywords: allergic rhinitis; immunoglobulin E; vitamin D; adult